The Standard of Ethics in Polish Enterprises - Irena DUDZIK-LEWICKA (Communications of International Proceedings, 2021)
Ethics in business is a commonly acknowledged business concept that plays a key role in many enterprises in the world. However, when it comes to business ethics, Polish companies, especially small and medium ones, there is much to be done. Undoubtedly, the importance of ethics in business is bound to grow and this means that ethics-related programs implemented in business entities will cease to be just an option, but instead will become a necessity. Therefore, the author makes use of her literary output with the outcome of other studies in order to verify the current mainstream approach towards the ethical concept in Polish enterprises.
Keywords: Ethics; Values; Business; Behavior; Poland.